2019
DOI: 10.1016/j.stemcr.2019.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Safety, Immunologic Response, and Imaging Outcomes following Neural Stem Cell Transplantation for Pelizaeus-Merzbacher Disease

Abstract: Summary Four boys with Pelizaeus-Merzbacher disease, an X-linked leukodystrophy, underwent transplantation with human allogeneic central nervous system stem cells (HuCNS-SC). Subsequently, all subjects were followed for an additional 4 years in this separate follow-up study to evaluate safety, neurologic function, magnetic resonance imaging (MRI) data, and immunologic response. The neurosurgical procedure, immunosuppression, and HuCNS-SC transplantation were well tolerated and all four subjects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 15 publications
1
31
0
Order By: Relevance
“…Briefly, bone marrow stromal cells (MSCs) are potentially useful for the treatment of a number of brain injury diseases due to their abundant supply. An increasing number of studies have reported their prospective functions and applications (9,(12)(13)(14)(15)(16)(17). In the present study, 758 miRNAs were detected in exosomes of MSCs using Agilent miRNA chip technology, where rno-miR-32-3p, rno-miR-211-3p, rno-miR-188-5p and rno-miR-465-5p were first found in the exosomes of MSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, bone marrow stromal cells (MSCs) are potentially useful for the treatment of a number of brain injury diseases due to their abundant supply. An increasing number of studies have reported their prospective functions and applications (9,(12)(13)(14)(15)(16)(17). In the present study, 758 miRNAs were detected in exosomes of MSCs using Agilent miRNA chip technology, where rno-miR-32-3p, rno-miR-211-3p, rno-miR-188-5p and rno-miR-465-5p were first found in the exosomes of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that treated rats had significantly recovered motor function. However, immune reactions induced by neural stem cell application and the resulting rejection continue to be the main challenges obstructing their current clinical application ( 8 , 9 ). Therefore, it is important to understand the mechanism underlying the suppression of immune-related cell activity during neural stem cell transplantation ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the transplantation of myelin-producing progenitor cells in patients with PMD was largely ineffective. The closer analysis of clinical data revealed a possible myelination only at a narrow area of implantation site [14,15]. Indeed, we have recently shown in a mouse model of demyelination (shiverer mice; MBP shi/shi , which were also immunode cient to avoid graft rejection; rag2 −/− ), that a robust therapeutic effect of human glial restricted precursors (hGRPs) correlates well with their distribution throughout the entire mouse brain, while mouse GRPs (mGRPs) characterized by limited migration, failed to provide any therapeutic effect [16].…”
Section: Introductionmentioning
confidence: 93%
“…Depending on the magnitude of disease progression or injury in the host tissue, the microenvironment may be void of trophic support that encourages cell engraftment and function, or even contain inflammatory or toxic factors secreted from reactive astrocytes [ 98–100 ] or microglia that contribute to graft rejection by the host immune system in the CNS, especially for allogeneic cell grafts. [ 101–104 ] Subsequently, over longer timescales after implantation, cells that do not innervate or migrate outward from the injection site or seek out vasculature may function suboptimally, if at all, due to insufficient oxygen/nutrient exposure and thereby reduce the potency of the overall cell graft. [ 105 ]…”
Section: Materials To Facilitate Cell Therapy For the Cnsmentioning
confidence: 99%